2015
DOI: 10.1246/cl.140962
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fluorescence of Loosely Packed Dye Aggregates

Abstract: The fluorescence of a hemicyanine dye was considerably enhanced by the formation of loosely packed aggregates, compared to tightly aggregated and molecularly dispersed hemicyanine dyes. Loose dye aggregates were realized by introducing a self-assembling unit to the dye molecules and by adjusting the mixture of good solvent and nonsolvent for the dye moiety.The aggregation morphology of organic dyes can greatly affect their fluorescence intensity, wavelength, and lifetime. For example, when arranged in a parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Fluorescence spectra of the TCPP compounds depicted two bands, which are consistent with literature studies for free base porphyrins (Figure B). , Both bands contained in the fluorescence spectra of TCPP nanoGUMBOS were red-shifted and displayed enhanced fluorescence intensity as compared to that of the parent dye. Fluorescence enhancement in nanoGUMBOS samples was attributed to formation of loosely packed dye aggregates which were produced by the presence of bulky and long alkyl chain phosphonium cations . Furthermore, fluorescence spectra of the nanoGUMBOS were better resolved as compared to the parent dye showing two distinct bands belonging to Q­(0,0) and Q­(0,1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence spectra of the TCPP compounds depicted two bands, which are consistent with literature studies for free base porphyrins (Figure B). , Both bands contained in the fluorescence spectra of TCPP nanoGUMBOS were red-shifted and displayed enhanced fluorescence intensity as compared to that of the parent dye. Fluorescence enhancement in nanoGUMBOS samples was attributed to formation of loosely packed dye aggregates which were produced by the presence of bulky and long alkyl chain phosphonium cations . Furthermore, fluorescence spectra of the nanoGUMBOS were better resolved as compared to the parent dye showing two distinct bands belonging to Q­(0,0) and Q­(0,1).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence enhancement in nanoGUMBOS samples was attributed to formation of loosely packed dye aggregates which were produced by the presence of bulky and long alkyl chain phosphonium cations. 31 Furthermore, fluorescence spectra of the nanoGUMBOS were better resolved as compared to the parent dye showing two distinct bands belonging to Q(0,0) and Q(0,1). NanoGUMBOS formed by use of the ion association method at a molar ratio of 1:1 exhibited fluorescence spectral shapes that contained characteristics of both nanoparticles composed of loosely packed aggregates and the monomer.…”
Section: Reprecipitation Of [P66614] 4 [Tcpp] and [P66614]mentioning
confidence: 97%
“…Also, over the long past, Schiff bases are recognized as efficient tools for the application of molecular sensors, nonlinear optics, and molecular switches for optical detection. , Keto–enol tautomerism is very common in Schiff bases having an alcoholic −OH group in the close vicinity in solution, but it is rather scarce in the solid phase. In the course of keto–enol tautomerism, intramolecular H-bonding plays a decisive role in exhibiting thermochromism and photochromism in the solution phase. In general, intramolecularly H-bonded cis -enol forms are more stable than the cis -keto forms in the ground states, but the cis -keto form remains stabilized with the rapid proton transfer known as keto–enol tautomerism in the excited states, which is mainly governed by the electronic environment of the imine group and the donor atom adjacent to it. , Thus, in most of the cases reported to date, the cis -keto form was found to be more stable in the excited states at room temperatures in keto–enol tautomerism. , However, this stabilization is strongly dependent on the nature and polarity of the solvents used. Generally, the cis -enol form is more stable in nonpolar solvents and the corresponding keto form in polar solvents. Moreover, J- or H-type aggregation becomes promising due to the cis-arrangement, which in turn makes the molecule rigid to rotational or vibrational motion. , This restriction of motion resulted in the radiative decay of energy and ultimately strong fluorescence in solid and solution or aggregate state. …”
Section: Introductionmentioning
confidence: 99%
“…Although the excited-state intramolecular proton transfer (ESIPT) phenomenon is of wide interest due to its stimulating photochemical and photophysical applications, the thoughtful insight of the equilibrium between cis- enol and cis -keto and then to trans -keto form in the solid phase upon heating has not been available thus far with in-depth interpretation both theoretically and experimentally. Yet again, dual-channel sensing of cations of biological importance like Al 3+ and Zn 2+ is important, and a considerable amount of work has been done in this respect in the solution/aqueous phase. Simultaneous detection of multiple analytes is important for the selective and sensitive probe as these save time, cost, and effort.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 We prepared G-Por by coupling synthesized N 2 ,N 3didodecyl-L-glutamide (G) with 5-(4-carboxyphenyl)-10,15,20triphenyl-21H,23H-porphine and subsequent insertion of zinc according to previously reported methods. 6,7 Confocal microscopy showed that a solution of G-Por in cyclohexane contains globular images, as revealed through the fluorescence of the porphyrin moiety (Figure 1b). The globular aggregation morphology is unusual given that G-derivatives often produce fibrils.…”
mentioning
confidence: 99%